Reflections of a Russian statesman - Pobedonostsev, Konstantin Petrovich (The Russian library, 1898)
Church and state.- The new democracy.- The great falsehood of our time.- Trial by jury.- The press.- Public instruction.- The law.- The malady of our time.- Knowledge and work.- Faith.- The ideals of unbelief.- The new religion and the new marriage.- The spiritual life.- The church.- Characters.- Power and authority.